2010
DOI: 10.1021/jo100727j
|View full text |Cite
|
Sign up to set email alerts
|

C−H Bonds as Ubiquitous Functionality: A General Approach to Complex Arylated Imidazoles via Regioselective Sequential Arylation of All Three C−H Bonds and Regioselective N-Alkylation Enabled by SEM-Group Transposition

Abstract: Imidazoles are an important group of the azole family of heterocycles frequently found in pharmaceuticals, drug candidates, ligands for transition metal catalysts, and other molecular functional materials. Owing to their wide application in academia and industry, new methods and strategies for the generation of functionalized imidazole derivatives are in demand. We here describe a general and comprehensive approach for the synthesis of complex aryl imidazoles, where all three C–H bonds of the imidazole core ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
89
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(93 citation statements)
references
References 64 publications
(44 reference statements)
2
89
0
2
Order By: Relevance
“…While this was encouraging, this meant that an exchange of imidazole N-substituents was necessary and that this had to be accomplished in a position selective manner. Fortunately, Robiette, 30 Sames 31 and more recently Knochel 17b have demonstrated that the DMAS-protecting group can be removed with a methyl group via the intermediacy of an imidazolium salt formed by reaction with methyl triflate or Meerwein’s salt. Given this encouraging precedent, the corresponding DMAS-protected 4,5-diiodoimidazole was used as a starting material.…”
Section: Resultsmentioning
confidence: 99%
“…While this was encouraging, this meant that an exchange of imidazole N-substituents was necessary and that this had to be accomplished in a position selective manner. Fortunately, Robiette, 30 Sames 31 and more recently Knochel 17b have demonstrated that the DMAS-protecting group can be removed with a methyl group via the intermediacy of an imidazolium salt formed by reaction with methyl triflate or Meerwein’s salt. Given this encouraging precedent, the corresponding DMAS-protected 4,5-diiodoimidazole was used as a starting material.…”
Section: Resultsmentioning
confidence: 99%
“…[15] Die elektrophile Bromierung des geschützten Imidazols konnte unter kontrollierten Bedingungen und in hohen Ausbeuten in MeCN mit NBS erreicht werden. Kommerziell erhältliches 4-Fluoracetophenon wurde in a-Stellung bromiert (6)u nd mit S-Methylthiopseudoharnstoff cyclisiert und ergab das Imidazol 7 in moderaten Ausbeuten.…”
Section: Methodsunclassified
“…Murai and Shibahara [123] also synthesized this target via sequential C-H arylation from a simple imidazole using their robust catalyst, [Pd(phen) 2 ](PF 6 ) 2 . Sames [125] also reported multiple arylations of simple imidazoles using his own catalytic system.…”
Section: Application Of 13-azole C-h Arylation To Target-oriented Symentioning
confidence: 99%